Supporting model reuse in organic reaction simulation: towards the compositional modelling approach - Tang, A.Y.C.; Zain, Sharifuddin Md (2012)
Model formulation and model reuse are among the challenges in the field of qualitative reasoning research. In organic reactions, there are many task-level chemical processes. Identifying the generic ones can help promote model reuse in a qualitative simulation environment. This paper describes an approach to automate qualitative models and reuse them for the simulation of a group of organic reactions for learning purposes. In particular, this paper describes how the generic processes are identified and used for the simulation of task-level processes. The generic processes were identified as “make-bond” and “break-bond”. In this work, chemical processes are represented as model fragments using the Qualitative Process Theory (QPT) ontology. The work applied compositional modelling technique to chain model fragments when predicting the final products of organic chemical reactions.